PENGARUH TEKANAN PANAS TERHADAP KELELAHAN PEKERJA - Margaretha .; Imam Thohari; Marlik . (Poltekkes Kemenkes Surabaya, 2019)
Fatigue is a condition of decreased efficiency and decreased work capacity and endurance. Fatigue can be influenced by individual factors such as age, length of work and nutritional status. Fatigue can also be influenced by physical environmental factors, namely heat pressure. The purpose of this study was to know the influence of heat pressure on fatigue in workers in the workshop of Sub Assembly, Assembly MPL and Assembly CBL PT. X Year 2019.This type of research is observational analytic with research design using Cross Sectional approach. a sample size of 34 workers. Data analysis was performed by univariate analysis and bivariate test with a statistical test namely Chi Square Test.Research results on workers in the Commercial Ship Division of X mostly aged ≤ 40 years with 91.2% with working duration kerja 8 hours / day as much as 100%, having fat nutritional status as much as 58.8%, heat exposure did not meet the requirements as much as 58.8% and experienced fatigue as much as 88 , 2%. The results of statistical tests using the Chi Square test showed p value equal to 0,039 (p value ≤ 0,05) which means there is an influence of heat pressure on the fatigue of workers in the Merchant Marine Division of PT. X in 2019.It is recommended to add an air ventilation place in the form of a window, adding a blower and workers often consume drinking water provided by the company. Keywords: Heat Pressure, Fatigue